The Relationship Between Learning Attitude And Conceptual Understanding Of Physics Students On Newton’s Laws Material - Ni Luh Apriani; Syamsu, Syamsu; Nurasyah Napitupulu, Dewi; Alit Adi Untara, Ketut (Al-Khazini, 2026)
The purpose of this study was to determine the relationship between learning attitude and understanding of the physics concept of students on the material of Newton's law at SMA Negeri 5 Palu. The method used in this research is correlational method with quantitative approach. Sampling using purposive sampling technique with a total sample of 33 students at SMA Negeri 5 Palu in the 2024/2025 school year. Data were collected through the acquisition of questionnaire scores and tests of students' concept understanding on Newton's Law material. Hypothesis testing in this study using Pearson correlation test. Based on the correlation test, it is found that the correlation test results referring to the Sig. (2-tailed) significance value of 0.00 < 0.05 then the two variables are declared correlated. With a correlation value of both of 0.639, this means that there is a significant relationship between the attitude of learning and understanding the physics concepts of students on Newton's law material, with a strong correlation degree and the acquisition of a determination value of 40.1%.